Communication Patterns of Counselors with Counseling Patients at the Cilegon City National Narcotics Agency - Prasojo; Arviani, Heidy (Universitas Islam Balitar, 2024)
The research explains the communication patterns of counselors with counseling patients of the Cilegon City National Narcotics Agency, with the highest number of adolescent drug addicts in Banten province. The research used a descriptive qualitative approach with in- depth interview techniques to explore informant data. Counseling communication patterns between counselors and counseling patients are the object of research. The research informant selection technique uses purposive sampling or informant determination technique with certain considerations. The main informants in the research are counseling patients and counselors at BNNK Cilegon who are in charge of rehabilitating adolescent drug abuser patients. The results revealed that the counseling communication pattern at BNNK Cilegon is included in the circular pattern, the message interaction process takes place in two directions and the communicant actively conveys message feedback. Counselors apply a counseling technique called client-centered therapy which is based on the equality of counselors and patients, the counseling program at BNNK Cilegon is divided into interpersonal counseling sessions for counselors and patients, family support sessions, and group therapy. This research is expected to be able to provide an overview of interactive counseling communication patterns, as well as provide perceptions to embrace drug addicts to escape drug addiction.